2017
DOI: 10.3389/fnins.2017.00701
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Power but Preserved Bursting Features of Subthalamic Neuronal Signals in Advanced Parkinson's Patients under Controlled Desflurane Inhalation Anesthesia

Abstract: Deep brain stimulation (DBS) surgery of the subthalamic nucleus (STN) under general anesthesia (GA) had been used in Parkinson's disease (PD) patients who are unable tolerate awake surgery. The effect of anesthetics on intraoperative microelectrode recording (MER) remains unclear. Understanding the effect of anesthetics on MER is important in performing STN DBS surgery with general anesthesia. In this study, we retrospectively performed qualitive and quantitative analysis of STN MER in PD patients received STN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Under desflurane inhalation, Lin et al observed that MER could be performed with a typical neuronal firing pattern and motion-related firing of STN, and the clinical results were similar in both groups [34,96].…”
Section: Is Mer Mandatory For Stn Dbs Surgery?mentioning
confidence: 98%
“…Under desflurane inhalation, Lin et al observed that MER could be performed with a typical neuronal firing pattern and motion-related firing of STN, and the clinical results were similar in both groups [34,96].…”
Section: Is Mer Mandatory For Stn Dbs Surgery?mentioning
confidence: 98%
“…In this context, a brain shift is produced when the burr holes are made [ 6 ]. The MERs signals amplitudes can vary from 50 µV up to 200 µV [ 8 , 9 , 10 ], and they are visually and acoustically analyzed, which requires a clean and crisp signal. Accordingly, signal conditioning must be done before starting the records, while using the pre-amplification module and software gain and filters in the set-up stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated changes in microelectrode signals under general anesthesia [17,39], several groups have attempted using different regimens of general anesthesia under which MER can still be recorded from STN. These techniques included using less than 1% Sevoflurane concentration [45], a combination of inhalational nitrous oxide and isoflurane or intravenous propofol and remifentanil [8], desflurane inhalation [46,47] sustaining the minimal alveolar concentration below 1% during MER [48]. These findings along with our current findings emphasize importance of anesthetic dose concentration and timings on the neurophysiological recordings.…”
Section: Discussionmentioning
confidence: 57%